Interlinkages Between Agri-Food Trade and the SDGs at the Global, Regional and Local Level - Ralph, Armah N. A.; Peter, Quartey; Festus, Turkson Ebo; Emmanuel, Abbey N.; Butu, Mawuenyega M.; Ellen, Huan‐Niemi (John Wiley & Sons, 2025)
This study is a structured review on the interlinkages between agri-food trade and the SDGs in the environmental, social and economic dimensions to identify any missed opportunities that agri-food trade could positively impact the SDGs and provide policy guidance for the missed opportunities at the global, regional and national levels. A great deal of diversity in the papers at the global level, and papers at the regional level are similar, but there is additional analysis on promoting regional markets and value chains. Papers at the local level are product-specific to emphasise how the trade of specific agricultural commodities would affect the achievement of particular SDGs in question. There is a concern regarding whether agri-food trade can promote sustainability and the attainment of the SDGs. This is particularly important given that gains from trade are not entirely equitable. Questions relating to concrete innovations, policies and behavioural changes that can ensure systemic transformations remain critical and need to be addressed.
Keywords: Agri-food; trade; SDGs; environmental; social; economic; opportunities; guidance